ANALISIS FAKTOR-FAKTOR PENDAPATAN PREMI, BEBAN KLAIM, DAN INVESTASI ASURANSI TERHADAP PDB DI INDONESIA - Sativa, Fajri Sena; Rivai, Aswin (Journal of Economics and Regional Science, 2026)
GDP is an econometric variable useful for understanding a country's economic growth. The insurance industry in Indonesia faces challenges, with the insurance penetration rate reaching only 2.59% by the end of 2023. This illustrates significant challenges in increasing the sector's contribution to the national economy. This study analyzes the impact of premium income, claim expenses, and insurance investments on Indonesia's GDP during the 2019-2023 period. A quantitative approach was used with panel data analysis techniques, encompassing 18 insurance companies registered with the Financial Services Authority (OJK). The results indicate that premium income and insurance investments have a significant positive impact on GDP, while claim expenses have an insignificant effect. Furthermore, simultaneous analysis reveals that all three variables collectively have a significant impact on Indonesia's economic growth. These findings highlight the critical role of the insurance sector in driving economic growth through increased liquidity and financial protection.